Minimally invasive approach of panfacial fractures - Wijaya, Yudi; Nurwiadh, R. Agus; Yuza, Abel Tasman; Fathurrahman, Fathurrahman (Padjadjaran Journal of Dentistry, 2015)
Background. Panfacial fractures involves fractures of several bones of face. They are associated with malocclusion, dish face deformity, enopthalmos, diplopia, cerebrospinal fluid leak and soft tissue injuries. Purpose. The purpose of this paper is to present a case of minimizing surgical wound and morbidity. Case. A 40 year old female presented with severe maxillofacial injuries caused by motor vehicle collisions about 5 days prior to admission. The assessment of the patient is mild head injury, panfacial fractures, lacerated wound at face, Â rupture of globe of occular sinistra. An open reduction and internal fixationÂ  (ORIF) and enucleation of globe occular sinistra was performed.Â  Intraoral vestibular incision is made in the upper and lower vestibular region. Mucoperiosteal flap elevation of vestibular will exposure of the anterior maxilla and mandibular fractures. Intermaksilary fixation within 3 week and restore aesthetic with prosthesis fitting eyeball and denture. Discusion. The goal ofÂ  treatment ofÂ  panfacial fracture is to restore both the functions and pre-injury 3-dimensional facial contours. To achieve this goal two commonÂ  sequences of management of Panfacial fractures are proposed, âBottom up and inside outâ or âTop down and outside inâ. Other sequences exist but there are variations of these two major approaches. Conclusion. A minimally invasive approach toÂ  the fracture site is an alternative methodÂ  to manage panfacial fracture with a simple, effective and lower complication rate.